Influence of Market Information on Decision to Invest through Nairobi Securities Exchange among Youth Groups of Kisumu County in Kenya - Kibegwa, John; Namiinda, Barbara; Nzioki, Susan (Research Gate, 2018)
The challenges associated with youth employment and participation in economic development has been a key concern world over, especially in developing economies. The youths in Kenya are specifically looked at because of the pivotal role that they play in the Kenyan economy and the emphasis the government has put on youth empowerment programs to enable them to improve their financial welfare and participate in economic development as a way of achieving the tenets of Vision 2030. The government through the youth enterprise fund has invested heavily in providing seed capital for youth willing to start their own businesses. The Nairobi securities exchange provides lucrative investment opportunities following the revolutionalization that has taken place in the market. However, the number of youth investing through it is still low. The CMA has also made significant efforts in enhancing access to market information by creating online platforms as well as the use of mobile phones and training programs for youth in universities and tertiary institutions. However there is a high population of youth staying in rural and urban areas organized into youth groups supported by government with seed capital programs such as the youth enterprise fund who may not have been reached out by these programs. This study therefore sought to analyze the investment patterns and the influence of market information on the youth’s decisions to invest through the NSE focusing on youth groups in Kisumu County. The study targeted the chairpersons of the youth groups or their representatives who were knowledgeable on the group investment strategies. The target population therefore was 380 chairpersons of youth groups from which a sample of 79 chairpersons was selected using stratified and random sampling method. Secondary data was obtained from the Youth Enterprise Fund, Nyanza Region for the four constituencies in Kisumu County while primary data was collected using questionnaires administered to the chair persons. The data collected was analyzed using descriptive statistics which included: mean, mode, frequencies and percentages while the relationships between market factors were determined using the t-statistics for two independence samples. The study revealed that market information had statistically significantly influence youth’s decisions to invest through the Nairobi Securities Exchange. The study therefore recommended that the Capital Markets Authority in Kenya should link the youth to platforms for accessing real-time capital markets data as well as empower them on how to use the data in making investment decisions.